Birds of a Feather? Probing Cross-National Variation in Nuclear Inhibitions. (1st January 2023) - Braut-Hegghammer, Målfrid
Abstract: What are the causes of cross-national variation in nuclear hawkishness? In the third nuclear age such variation is likely to be more consequential than in the past. While such variation has been observed, it has not been explained. This article probes possible causes of such variation drawing on a new wave of research on nuclear inhibitions. Specifically, I explore how the threat environment, domestic-level factors, and elite maneuvering, can affect nuclear hawkishness. I argue that hawkishness is less likely to be an outlier phenomenon among the more recent nuclear weapons states and in the broader universe of cases.